Using assessment for school improvement - James, Mary. (USA : Heinemann educational, 1998)
Designed to help school managers in the development and implementation of a whole-school assessment policy, this book poses important questions which need to be addressed and outlines the available options and their likely consequences.
Includes index.
Keywords: Educational tests and measurements -- Great Britain; School improvement programs -- Great Britain